2007
DOI: 10.1590/s0100-67622007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação do carbono estocado na parte aérea e raízes de Hevea sp., aos 12 anos de idade, na Zona da Mata Mineira

Abstract: 657RESUMO -Este trabalho foi desenvolvido com o objetivo de quantificar o carbono estocado nos diferentes componentes das árvores de Hevea sp., na fazenda experimental da Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG), no Município de Oratórios, Minas Gerais, servindo como base para verificar a importância da cultura no seqüestro de carbono e, conseqüentemente, na mitigação do efeito-estufa. Após as análises, verificouse que: a) os galhos contribuíram com a maior quantidade de carbono armazenado, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
6
1
4
Order By: Relevance
“…In contrast, the observed total C biomass was about 40, 17 and 18.6 % lower than the biomass values found by Cotta et al (2006), Fernandes et al (2007), and Maggiotto et al (2014), respectively. Though a lower total C biomass stock was found in our study compared to other studies, in general, the rubber tree plants in this study exhibited a C accumulation rate superior to that of other studies (Table 6).…”
Section: Aboveground Part Of the Rubber Tree As The Main C Pool Of Thcontrasting
confidence: 76%
See 3 more Smart Citations
“…In contrast, the observed total C biomass was about 40, 17 and 18.6 % lower than the biomass values found by Cotta et al (2006), Fernandes et al (2007), and Maggiotto et al (2014), respectively. Though a lower total C biomass stock was found in our study compared to other studies, in general, the rubber tree plants in this study exhibited a C accumulation rate superior to that of other studies (Table 6).…”
Section: Aboveground Part Of the Rubber Tree As The Main C Pool Of Thcontrasting
confidence: 76%
“…For example, in assessing a 20-year-old rubber plantation, Carmo et al (2006) reported that about 70 % of the estimated tree C biomass was accounted for by the branches, whereas 23.4 % was represented by the stem, and 7 % by the leaves. Similarly, Fernandes et al (2007), in assessing a 12-year-old rubber plantation, reported a higher contribution of branches to total C biomass (35 %) than the contributions made by stems (30 %), roots (30 %) and leaves (4 %). Such results do not agree with those observed in the present study.…”
Section: Aboveground Part Of the Rubber Tree As The Main C Pool Of Thmentioning
confidence: 91%
See 2 more Smart Citations
“…Dentre esses gases destaca-se o dióxido de carbono (CO 2 ), responsável por cerca de 60% da intensificação do efeito de estufa, uma vez que desde o início da revolução industrial as concentrações desse gás na atmosfera passaram de 280 ppm para cerca de 390 ppm. [1][2][3] Nos países em desenvolvimento, mudanças no uso e na cobertura da terra, especialmente em ambientes savânicos e florestais, são apontadas como uma das principais causas do aumento das concentrações de CO 2 atmosférico, uma vez que a substituição desses biomas nativos por atividades agrícolas leva ao aumento das emissões de CO 2 pelo solo. 4 As emissões de CO 2 pelo solo correspondem ao CO 2 produzido pela respiração das raízes e dos microrganismos presentes no solo, responsáveis pela decomposição aeróbica de matéria orgânica (MO), sendo influenciadas pelo tipo de vegetação presente, e pelas características do solo.…”
Section: Introductionunclassified